Studies of Metal Organic Networks via M-Polynomial-Based Topological Indices - Muhammad Tanveer Hussain; Muhammad Javaid; Sajida Parveen; Hafiz Muhammad Awais; Md Nur Alam (Journal of Mathematics)
Topological index (TI) is a graph-theoretic tool that is used to study different physical and structural properties of the networks in various disciplines of science such as computer science, chemistry, and information technology. In this article, we study transition metal tetra-cyano-benzene organic networks by computing their M-polynomials and various topological indices (TIs). At the end, a comparison is also included between all the computed degree-based topological indices to show their betterness.